A molecular phylogeny reveals paraphyly of the large genus Eulophia (Orchidaceae): A case for the reinstatement of Orthochilus. Issue 1 (27th January 2014) - Martos, Florent; Johnson, Steven D.; Peter, Craig I.; Bytebier, Benny
Abstract: Phylogenetic relationships were inferred for the African‐centred orchid subtribe Eulophiinae, which includes the large genus Eulophia and three closely related genera, Oeceoclades, Pteroglossaspis and Acrolophia . We sequenced one nuclear (ITS) and four chloroplast ( rbcL, trnK‐matK, rpl32‐trnL, trnQ‐5′ rps16 ) markers for 86 samples, representing 58 species (62 taxa) and one outgroup. The combined sequence matrix had 6525 characters and was analysed using parsimony and Bayesian criteria. Our results show that Acrolophia and Oeceoclades are monophyletic but are nested in Eulophia as currently circumscribed, thus rendering it paraphyletic. We argue for retaining Acrolophia and Oeceoclades, and splitting Eulophia into two genera on the basis of evidence that each of these four clades is genetically and morphologically distinct. We propose to reinstate the genus name Orthochilus for one of the Eulophia clades and transfer 35 taxa, including those assigned to Pteroglossaspis, to Orthochilus . Thirty‐two of these are new combinations.